Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s12987-022-00315-1
|View full text |Cite
|
Sign up to set email alerts
|

Dual effect of TAT functionalized DHAH lipid nanoparticles with neurotrophic factors in human BBB and microglia cultures

Abstract: Background Neurodegenerative diseases (NDs) are an accelerating global health problem. Nevertheless, the stronghold of the brain- the blood–brain barrier (BBB) prevents drug penetrance and dwindles effective treatments. Therefore, it is crucial to identify Trojan horse-like drug carriers that can effectively cross the blood–brain barrier and reach the brain tissue. We have previously developed polyunsaturated fatty acids (PUFA)-based nanostructured lipid carriers (NLC), namely DHAH-NLC. These c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 97 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…They quantitatively assessed the permeability of DHAH-NLCs in endothelial cells (BMECs). Successfully, they reported that TAT-functionalized DHAH-NLCs successfully crossed the BBB in a cellular model (Hernando et al, 2022).…”
Section: Lipid Nanoparticlesmentioning
confidence: 99%
“…They quantitatively assessed the permeability of DHAH-NLCs in endothelial cells (BMECs). Successfully, they reported that TAT-functionalized DHAH-NLCs successfully crossed the BBB in a cellular model (Hernando et al, 2022).…”
Section: Lipid Nanoparticlesmentioning
confidence: 99%
“…NPs, including polymer, dendrimer, lipid, extracellular vesicles, and inorganic nanoparticles, have been designed to deliver APIs to microglia in many different CNS disorders and studied in various models, including autism spectrum disorder, cerebral palsy, neuropathic pain, SCI, Alzheimer’s, experimental autoimmune encephalomyelitis (EAE), TBI, retinal degeneration, Rett syndrome, and stroke ( Iezzi et al, 2012 ; Sharma et al, 2017 , 2020 ; Ganbold et al, 2020 ; Khoury et al, 2020 ; Liao et al, 2020 ; Gao et al, 2021 ; Kim et al, 2021 ; Liu et al, 2021 ; He et al, 2022 ; Sepasi et al, 2023 ) ( Table 1 ). API payloads range from small molecule drugs to proteins, peptides, and siRNA ( Lee et al, 2021 ; Liu et al, 2021 ; Hernando et al, 2022 ; Zhang M. et al, 2023 ). Most NP API therapies aim to modulate the microglial inflammatory response, polarizing microglia towards the more neuronally protective M2 phenotype to alleviate the inflammatory response and improve functional outcomes ( Papa et al, 2013 , 2016 ; Lu et al, 2014 ; Nance et al, 2015 , 2017 ; Saxena et al, 2015 ; Kim et al, 2017 ; Wang Y. et al, 2018 ; Ellert-Miklaszewska et al, 2019 ; Cahalane et al, 2020 ; Cho et al, 2021 ; Xiao et al, 2021 ; Baghbanbashi et al, 2022 ; Ganbold et al, 2022 ; Guo et al, 2022 ; Hollinger et al, 2022 ; Shin et al, 2022 ; Ishida et al, 2023 ; Kalashnikova et al, 2023 ; Pu et al, 2023 ).…”
Section: Nanomaterials For Api Delivery To Cns Gliamentioning
confidence: 99%